<h2>
Answer: y + 7 = -3 (x - 1)</h2>
Step-by-step explanation:
The slope of the line (m) = (y₂ - y₁) ÷ (x₂ - x₁)
= (- 7 - 8) ÷ ( 1 - (- 4))
= - 15 ÷ 5
= - 3
We can now use the point-slope form to write the equation for this line:
y - y₁ = m(x - x₁) where (x₁ , y₁) = (1, -7)
y - (-7) = -3 ( x - 1)
y + 7 = -3 (x - 1)
X + 3y = 7
y = 2
Substitute
x + 3(2) = 7
x + 6 = 7
x = 1
Hope this helps!<span />
Answer:
x=48
Step-by-step explanation:
I hope I helped!!1
Answer:
363
Step-by-step explanation:
11x11=121
((11x11)÷2)x4=11x11x2=121x2=242
121+242=363